2014
DOI: 10.1016/j.psychres.2014.08.053
|View full text |Cite
|
Sign up to set email alerts
|

The critical warzone experiences (CWE) scale: Initial psychometric properties and association with PTSD, anxiety, and depression

Abstract: Objective-To develop and evaluate a Critical Warzone Experiences (CWE) scale, a brief measure of warzone experiences associated with the development of posttraumatic stress disorder (PTSD), anxiety, and depression.Method-The psychometric properties of the CWE were evaluated across three independent samples of Iraq/Afghanistan veterans (combined N = 392).Results-Despite its brevity (7 items), the CWE exhibited good internal consistency (average α = .83), good temporal stability (1-year test-retest reliability =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…A clinician administered TBI interview (Vasterling, 2008; Morissette et al, 2011) based on American Congress of Rehabilitation Medicine guidelines (Gerberding and Binder, 2003) was used to assess TBI. The Critical Warzone Experiences Scale (CWE; Kimbrel et al, 2014c) was used to assess combat exposure. Note that the PTSD, depression, alcohol dependence, TBI, NSSI, and SA variables used in the present analyses were all lifetime history variables.…”
Section: Methodsmentioning
confidence: 99%
“…A clinician administered TBI interview (Vasterling, 2008; Morissette et al, 2011) based on American Congress of Rehabilitation Medicine guidelines (Gerberding and Binder, 2003) was used to assess TBI. The Critical Warzone Experiences Scale (CWE; Kimbrel et al, 2014c) was used to assess combat exposure. Note that the PTSD, depression, alcohol dependence, TBI, NSSI, and SA variables used in the present analyses were all lifetime history variables.…”
Section: Methodsmentioning
confidence: 99%
“…The Critical Warzone Experiences scale (CWE; Kimbrel et al, 2014) is a 7-item measure of warzone experiences that are strongly associated with the development of psychopathology in Iraq/Afghanistan-era veterans. The CWE has good internal consistency, test-retest reliability, validity, and factor structure (Kimbrel et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The CWE has good internal consistency, test-retest reliability, validity, and factor structure (Kimbrel et al, 2014). In addition, Kimbrel et al (2015) have demonstrated that CWE scores are positively associated with a general measure of social anxiety symptomatology ( r = 0.36, p < .001) among Iraq/Afghanistan-era veterans.…”
Section: Methodsmentioning
confidence: 99%
“…The Critical Warzone Experiences scale (Kimbrel et al, 2014) is a 7-item version of the widely-used U.S. Army and Marine Corps Mental Health Advisory Team's Combat Experiences Scale (MHAT-CES), which has been used in numerous studies of Iraq/ Afghanistan veterans (e.g., Hoge et al, 2004;Morissette et al, 2011;Guyker et al, 2013). Kimbrel and colleagues (2014) found that the Critical Warzone Experiences scale demonstrated good internal consistency (average α = 0.83), good test-retest reliability (r = 0.73), and good concurrent validity with longer measures of combat and warzone experiences (average r = 0.74).…”
Section: Methodsmentioning
confidence: 99%